PEMBUKUAN BERBASIS ANDROID PADA KUBE BUNGA RAYA DESA GUNUNG KIJANG DENGAN APLIKASI SIAPIK - Andres Putranta Sitepu; Maryati Maryati; Agnes Edelia Safha Putri; Anugerah Ridho; Evyana Putri Sulfat; Irvan Maulana; Nur Afni Wahyuni (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this program is to make financial reports based on the Si Apik application for UMKM so that UMKM can be helped by this application. As an object, namely the Kube Bunga Raya Joint Business Group (Kube) located in Desa Gunung Kijang, Kecamatan Gunung Kijang, Kabupaten Bintan. The preparation of these financial reports uses Android and refers to SAK EMKM. The process of preparing financial reports is carried out for the period October 2022. The Si Apik application aims to record transactions and financial reports easily and simply, this application can be used every day and anywhere. The Si Apik application makes it easy for UMKM to apply for capital loans to financial institutions